2021
DOI: 10.1021/acs.macromol.0c02465
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Mechanism of the Large Electrocaloric Effect in Vinylidene Difluoride-Based Polymers

Abstract: The molecular mechanism of the large electrocaloric effect in ferroelectric vinylidene difluoride-based polymers was proposed. The mechanism involves the electric field-induced phase transition between the ferroelectric β-phase and the paraelectric conformationally disordered (condis) phase. The condis phase is characterized by the absence of a three-dimensional crystallographic order: there is only two-dimensional translational symmetry in the plane perpendicular to the chain direction. Due to conformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…That indicates the first order phase transition. Analysis of the chains conformations above and below the transition temperature performed in Ref 12 indicated that this is the phase transition from the ferroelectric β phase to the paraelectric condis phase. For visualization of fragments of poly(VDF‐co‐TrFE) chains in β and condis phase see Figure 3.…”
Section: Simulationsmentioning
confidence: 98%
See 4 more Smart Citations
“…That indicates the first order phase transition. Analysis of the chains conformations above and below the transition temperature performed in Ref 12 indicated that this is the phase transition from the ferroelectric β phase to the paraelectric condis phase. For visualization of fragments of poly(VDF‐co‐TrFE) chains in β and condis phase see Figure 3.…”
Section: Simulationsmentioning
confidence: 98%
“…The object of this study is poly(VDF‐ co ‐TrFE) copolymer with molar monomeric composition VDF:TrFE = 55:45, for which the electrocaloric effect was studied experimentally and both ΔT and remanent polarization as functions of temperature are available in literature 9 . As an initial system for the MD simulations, we prepared the β crystal of the copolymer with quasi‐infinite chains as described in Reference 12. The total monomer composition of the system was 1760 VDF +720 ( R )‐TrFE +720 ( S )‐TrFE.…”
Section: Simulationsmentioning
confidence: 99%
See 3 more Smart Citations